Chemical constituents and bioactivities of garcinia griffithii T. Anderson - Nik Shazwani Afifah Nik Sazali, 1989- author; Farediah Ahmad, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2014